2021
DOI: 10.1177/0956797620968792
|View full text |Cite
|
Sign up to set email alerts
|

Preregistered Replication of “Feeling Superior Is a Bipartisan Issue: Extremity (Not Direction) of Political Views Predicts Perceived Belief Superiority”

Abstract: There is currently a debate in political psychology about whether dogmatism and belief superiority are symmetric or asymmetric across the ideological spectrum. Toner, Leary, Asher, and Jongman-Sereno (2013) found that dogmatism was higher among conservatives than liberals, but both conservatives and liberals with extreme attitudes reported higher perceived superiority of beliefs. In the current study, we conducted a preregistered direct and conceptual replication of this previous research using a large nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In fact, we believe we could find similar neural results in other groups exposed to misinformation relevant to their own sacred values. For instance, a recent nationally representative sample of Americans found that people on the extreme left score higher in dogmatism (albeit not as far as those on the far right) and they may therefore be resistant to information that challenges their beliefs (see Harris et al 46 ). Finally, our study was a controlled experiment with artificially designed social media posts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we believe we could find similar neural results in other groups exposed to misinformation relevant to their own sacred values. For instance, a recent nationally representative sample of Americans found that people on the extreme left score higher in dogmatism (albeit not as far as those on the far right) and they may therefore be resistant to information that challenges their beliefs (see Harris et al 46 ). Finally, our study was a controlled experiment with artificially designed social media posts.…”
Section: Discussionmentioning
confidence: 99%
“…Participants not only sampled positively-biased information more readily, but also held the beliefs they formed on the basis of the predictions yielded by positively-biased sources in higher confidence. Previous work has shown that individuals with extreme beliefs tend to have higher confidence in their beliefs 27 , 28 . Here, we showed that those with the highest confidence in their beliefs about the world-state were those who were biased towards information sources that were positively-biased, rather than those sampling from more objectively accurate sources.…”
Section: Discussionmentioning
confidence: 96%
“…The potential effects of the hedonic pursuit of desirable information on the beliefs we form are also poorly understood. Individuals with the most extreme beliefs have been shown to have the greatest confidence in their beliefs 27 , 28 . This may be driven by mental rigidity, which has been shown to co-occur both with extreme beliefs and the preference for congenial information 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Scientists can therefore select different issues to show, alternatively, that people on the left or right of the political spectrum are more prone to a sense of superiority about their beliefs. It is only when looking across multiple topics that the overall quadratic relationship emerges (Harris & Van Bavel, 2021), suggesting the people on both ends of the spectrum are similarly prone to feelings of superiority when their attitudes are extreme.…”
Section: Introductionmentioning
confidence: 99%